Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference 2022
DOI: 10.52041/iase.icots11.t14d3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Statistics Anxiety in Several Introductory Statistics Courses to Understand Differences Between Types of Students and Types of Courses

Abstract: Despite its importance in modern curricula, many students find statistics courses challenging, and the existence of barriers among students to learning statistical reasoning is an important area of study. This study explores the presence and level of statistics anxiety in several cohorts of students studying introductory statistics. The relationship with statistical anxiety dependent on specialisms is explored, along with their curricular choices. An online questionnaire was developed to explore the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Accordingly, it was of interest to explore how 'specialism' and 'compulsion' related to statistics anxiety. This is what Bock et al (2020) and Alexander et al (2022) explored and report on, and that original SoTL enquiry is the focus of our reflections here.…”
Section: Background: the Original Sotl Enquiry Exploring Statistics A...supporting
confidence: 69%
See 4 more Smart Citations
“…Accordingly, it was of interest to explore how 'specialism' and 'compulsion' related to statistics anxiety. This is what Bock et al (2020) and Alexander et al (2022) explored and report on, and that original SoTL enquiry is the focus of our reflections here.…”
Section: Background: the Original Sotl Enquiry Exploring Statistics A...supporting
confidence: 69%
“…The project reported in Bock et al (2020) and Alexander et al (2022) identified several statistically significant results and several meaningful results. Statistically significant results included females enduring higher anxiety scores compared to males, and Chinese learners enduring lower anxiety rates compared to British and Irish learners.…”
Section: The Academic Developer's Viewmentioning
confidence: 93%
See 3 more Smart Citations